Monitoring Vegetation Characteristics and Degradation Risk in Jordan Using NDVI Time Series - Makhamreh, Zeyad (Dirasat: Human and Social Sciences, 2019)
Satellite derived indices e.g. NDVI have been widely used for vegetation analysis and change detection studies at different spatial scales. This study analyses the vegetation characteristics and impact of long-term variation in vegetation cover upon land degradation in Jordan. The inclination and significance of NDVI trends, which are derived from the Modified Seasonal Mann-Kendall and the Seasonal Kendall Slope, are used to determine the hotspot of vegetation degradation during the period 1989-2004. The analysis shows that the mountain regions are more vulnerable for vegetation degradation than other ecological regions due to climate variability, urban expansion, and changes in land use systems. The effect of climate variability and the impact of improper land use on the natural ecosystem in the transitional zone are becoming more vulnerable to land degradation. The vulnerability of the irrigated farms to degradation in the Jordan valley is mainly due to the fluctuations in available water for irrigation, while the pattern of ground water utilization has important effect on vegetation distribution in the desert regions. However, in the Desert regions, the NDVI trend components are not significant as the value of vegetation density is very low. It is noticeable that the land degradation triggered by rainfall variability, urban growth, expansion of irrigation, and socio-economic transformations.